Keragaman Morfologi Daun Padi Lokal Indonesia dan Korelasinya dengan Ketahanan Penyakit Hawar Daun Bakteri - Wage Ratna Rohaeni; Dini Yuliani (Institut Pertanian Bogor, 2019)
Bacterial leaf blight (BLB) is one of the major diseases of rice plants mainly in irrigated rice caused by pathogenic bacteria Xanthomonas oryzae pv. oryzae (Xoo). Leaf morphology becomes an interesting character to be investigated due to its relationship with the intensity of BLB disease, because the leaf is the part of plant which is infected by the bacteria. The purpose of this research was to obtain information on the variability of leaf morphology and its correlation with BLB diseases, to support plant breeding program of BLB disease-resistant rice varieties. A total of 25 local rice accessions were characterized phenotypically. Leaf morphological characters were examined without replication, while in Xoo resistance (pathotype IV) test was done by using randomized block design with three replications. Characterization on leaf morphology indicated that all local rice accessions had green collar, transparent auricle color, white ligule color, and 2-cleft ligule shape. In four weeks after inoculation, four accessions (Ketan Lomah Hitam, Bumbuy Inih, Gonggoi, and Waren) showed disease severity percentages of BLB diseases on the range between 13-16%. These observations indicated that these accessions had slightly sussceptible response to BLB diseases wich were better than the other accessions. Leaf-surface morphology was positively correlated with BLB disease. The four accessions were feathery or slightly hairy with a short-sized leaf. The results of this research could be used as a reference for developing of BLB resistance rice varieties.